1974
DOI: 10.1104/pp.54.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Regulation of Water Transport in Some Woody and Herbaceous Species

Abstract: The efficiency with which plants transport water is related to the water potential differences required to drive water fluxes from the soil to the leaf. A comparative study of The extent to which climatic, plant, and edaphic factors influence plant-water balance and plant-water use is both complex and of considerable adaptive significance. Analyses of water movement in the soil-plant-atmosphere continuum and of the development of plant-water stress are facilitated by interpreting plant responses to variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
45
1
3

Year Published

1975
1975
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(63 citation statements)
references
References 13 publications
11
45
1
3
Order By: Relevance
“…All the tree species surveyed have low K p (Fig. 2), which is in agreement with previous work showing that, in general, hydraulic conductance is lower in trees than in herbs (Camacho-B et al, 1974;Iovi et al, 2009). Compared with herbs, trees have lower root density (Newman, 1969;Atkinson, 1980) and a much longer and more convoluted flow path (Tyree and Ewers, 1991), both of which contribute to larger wholeplant hydraulic resistance (lower K p ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…All the tree species surveyed have low K p (Fig. 2), which is in agreement with previous work showing that, in general, hydraulic conductance is lower in trees than in herbs (Camacho-B et al, 1974;Iovi et al, 2009). Compared with herbs, trees have lower root density (Newman, 1969;Atkinson, 1980) and a much longer and more convoluted flow path (Tyree and Ewers, 1991), both of which contribute to larger wholeplant hydraulic resistance (lower K p ).…”
Section: Discussionsupporting
confidence: 79%
“…2 and 4). These active loading herbs represent most of the herbaceous plants, which are characterized by high K p and low foliar Suc concentration (Camacho-B et al, 1974;Iovi et al, 2009;Rennie and Turgeon, 2009). Indeed, the low foliar sugar concentration of herbs is one of their signature features.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work with well watered sesame plants had demonstrated that leaf resistance increased when the humidity gradient between leaf and air was increased with bulk leaf water status remaining relatively constant (3) and that leaf resistance responded more to humidity gradients at lower temperatures (12). Interactions between the effects of humidity gradients, temperature, and CO2 concentration on leaf resistance and the effects of humidity gradients on mesophyll resistance to CO are described in this paper.…”
mentioning
confidence: 93%
“…caused by changes in bulk leaf water status (3,12,16,23). This response system would provide an adaptive advantage in arid environments because it could prevent the development of water stress in the metabolically active cells within the leaf (23), and because it would promote the efficient use of water by plants (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation